2014
DOI: 10.1038/ajg.2014.132
|View full text |Cite
|
Sign up to set email alerts
|

Mortality From Chronic Liver Diseases in Diabetes

Abstract: OBJECTIVES:Mortality from chronic liver diseases (CLDs) is increased in diabetes, but little is known about the etiology. The aim of this study was to assess mortality rates from CLD by etiology in known diabetic subjects living in the Veneto Region, Northern Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 30 publications
6
90
3
6
Order By: Relevance
“…For instance, the risk of severe liver disease was moderately increased in men with a BMI of ≥30 kg/m 2 free of T2DM (HR 2.09, 95% CI 1.72 to 2.54), but substantially higher in men with a BMI of ≥30 kg/m 2 and T2DM (HR 3.28, 95% CI 2.27 to 4.74). T2DM has consistently been shown to be associated with an increased risk of cirrhosis14 25 and our results show that this is the case irrespective of the BMI in late adolescence. However, an increased risk for severe liver disease was also seen in a dose-response manner for a higher BMI in men free of T2DM during the follow-up, suggesting that the association between a high BMI in late adolescence and future severe liver disease cannot solely be explained by development of T2DM.…”
Section: Discussionsupporting
confidence: 66%
“…For instance, the risk of severe liver disease was moderately increased in men with a BMI of ≥30 kg/m 2 free of T2DM (HR 2.09, 95% CI 1.72 to 2.54), but substantially higher in men with a BMI of ≥30 kg/m 2 and T2DM (HR 3.28, 95% CI 2.27 to 4.74). T2DM has consistently been shown to be associated with an increased risk of cirrhosis14 25 and our results show that this is the case irrespective of the BMI in late adolescence. However, an increased risk for severe liver disease was also seen in a dose-response manner for a higher BMI in men free of T2DM during the follow-up, suggesting that the association between a high BMI in late adolescence and future severe liver disease cannot solely be explained by development of T2DM.…”
Section: Discussionsupporting
confidence: 66%
“…For example, Zoppini et al recently reported that, compared to the age and sex-matched general population, T2DM patients had an approximately three-fold higher risk of dying of non-viral and non-alcoholic chronic liver disease, thus largely attributable to NAFLD. 118 In agreement, a study of 337 T2DM patients reported that NAFLD carried a two-fold increased risk of all-cause mortality (malignancy, CVD and liver-related complications) during a mean 11-year follow-up. 119 Growing evidence suggests that NAFLD is associated not only with liver-related morbidity or mortality, but also with an increased risk of developing CVD, i.e., the most common cause of death in T2DM.…”
supporting
confidence: 57%
“…Patients with NAFLD and T2D have a high prevalence of NASH and advanced fibrosis[3,15,57-59], and consistently, T2D is a strong predictor of the severity and progression of histologically assessed hepatic fibrosis[25,27,57,60]. Moreover, T2D is also an important predictor of the development of HCC[61,62] and an increased risk of all-cause and liver-related mortality[60,63,64]. …”
Section: Nafldmentioning
confidence: 99%